Whole Genome Sequencing of Fusarium fujikuroi Provides Insight into the Role of Secretory Proteins and Cell Wall Degrading Enzymes in Causing Bakanae Disease of Rice - Bashyal, Bishnu M.; Rawat, Kirti; Sharma, Sapna; Kulshreshtha, Deepika; Gopala Krishnan, S.; Singh, Ashok K.; Dubey, Himanshu; Solanke, Amolkumar U.; Sharma, T. R.; Aggarwal, Rashmi (Frontiers in Plant Science, 2017)
Fusarium fujikuroi causing bakanae disease has emerged as one of the major pathogen of rice across the world. The study aims to comparative genomic analysis of Fusarium fujikuroi isolates and identification of the secretary proteins of the fungus involved in rice pathogenesis. In the present study, F. fujikuroi isolate “F250” was sequenced with an assembly size of 42.47 Mb providing coverage of 96.89% on reference IMI58289 genome. A total of 13,603 protein-coding genes were predicted from genome assembly. The average gene density in the F. fujikuroi genome was 315.10 genes per Mb with an average gene length of 1.67 kb. Additionally, 134,374 single nucleotide polymorphisms (SNPs) are identified against IMI58289 isolate, with an average SNP density of 3.11 per kb of genome. Repetitive elements represent approximately 270,550 bp, which is 0.63% of the total genome. In total, 3,109 simple sequence repeats (SSRs), including 302 compound SSRs are identified in the 8,656 scaffolds. Comparative analysis of the isolates of F. fujikuroi revealed that they shared a total of 12,240 common clusters with F250 showing higher similarity with IMI58289. A total of 1,194 secretory proteins were identified in its genome among which there were 356 genes encoding carbohydrate active enzymes (CAZymes) capable for degradation of complex polysaccharides. Out of them glycoside hydrolase (GH) families were most prevalent (41%) followed by carbohydrate esterase (CE). Out of them CE8 (4 genes), PL1 (10 genes), PL3 (5 genes), and GH28 (8 genes) were prominent plant cell wall degrading enzymes families in F250 secretome. Besides this, 585 genes essential for the pathogen–host interactions were also identified. Selected genes were validated through quantitative real-time PCR analyses in resistant and susceptible genotypes of rice at different days of inoculation. The data offers a better understanding of F. fujikuroi genome and will help us enhance our knowledge on Fusarium fujikuroi–rice interactions.